A single-molecule van der Waals compass - Shen, Boyuan; Chen, Xiao; Wang, Huiqiu; Xiong, Hao; Bosch, Eric G. T.; Lazić, Ivan; Cai, Dali; Qian, Weizhong; Jin, Shifeng; Liu, Xin; Han, Yu; Wei, Fei (Nature (London), 2021)
Single-molecule imaging is challenging but highly beneficial for investigating intermolecular interactions at the molecular level 1 – 6 . Van der Waals interactions at the sub-nanometre scale strongly influence various molecular behaviours under confinement conditions 7 – 11 . Inspired by the traditional compass 12 , here we use a para -xylene molecule as a rotating pointer to detect the host–guest van der Waals interactions in the straight channel of the MFI-type zeolite framework. We use integrated differential phase contrast scanning transmission electron microscopy 13 – 15 to achieve real-space imaging of a single para -xylene molecule in each channel. A good correlation between the orientation of the single-molecule pointer and the atomic structure of the channel is established by combining the results of calculations and imaging studies. The orientations of para -xylene help us to identify changes in the van der Waals interactions, which are related to the channel geometry in both spatial and temporal dimensions. This work not only provides a visible and sensitive means to investigate host–guest van der Waals interactions in porous materials at the molecular level, but also encourages the further study of other single-molecule behaviours using electron microscopy techniques. The orientation of a rotating para -xylene molecule in the nanochannel of a zeolite framework can be visualised by electron microscopy to determine the host–guest van der Waals interaction inside the channel.